Blackwell’s five-minute veterinary consult clinical companion - Horwitz, Debra F. (Blackwell Pub., 2007)
This manual is designed as a quick reference for veterinarians and students alike. Information is readily available in a practical and easy-to-use format, with topics organized alphabetically for easy reference. Coverage includes typical problem behaviors in dogs and cats, such as various types of aggression, anxiety, fear, soiling and marking, vocalizing, and destructive behaviors. Appendices provide additional resources on psychopharmacology, learning and behavior modification, and client handouts. An accompanying CD-ROM also offers electronic versions of handouts for easy use